Exploring Stakeholder Perceptions and Motivations towards Adopting Waqf Blockchain: Waqif's perceived intentions - Mokthar, Mohammad Zulfakhairi; Sapuan, Noraina Mazuin (2023)
The study aims to gain insight into the adoption of waqf blockchain in Malaysia. In order to achieve this purpose, this study is conducted to examine factors influencing endowers perceived intention to adopt waqf blockchain in Malaysia. This study adopts UTAUT as the research framework and uses a survey research design. The sample for this study was collected using non-probability sampling as the sample frame is unknown, and data was collected through questionnaires distributed throughout Malaysia. The collected data were then analyzed using SmartPLS software. The main findings suggest that performance expectancy, social influence, and facilitating conditions play a positive role in explaining the perceived intention to adopt waqf blockchains among endowers in Malaysia.